1997
DOI: 10.1155/tsm.32.41
|View full text |Cite
|
Sign up to set email alerts
|

Band Structure Formation in Metals Under Deformation

Abstract: The study of the specific features of the flow of different metal layers at the deformation zone during rolling suggests that a regular banded structure of the material is determined by corrugation of some of its layers subject to strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Whereas in samples with low V ns an almost uniform laminar material flow is observed, in samples with high V ns (samples 9, 11 and 29) in regions where coarse particles accumulate the material flow becomes wave-like leading to the so-called ''crimping'' of the microstructure. It is known that crimping is caused by a non-uniform deformation in different layers of the material [26]. It is more prominent at 940°C where the wave amplitude is maximal (Fig.…”
Section: Microstructurementioning
confidence: 99%
“…Whereas in samples with low V ns an almost uniform laminar material flow is observed, in samples with high V ns (samples 9, 11 and 29) in regions where coarse particles accumulate the material flow becomes wave-like leading to the so-called ''crimping'' of the microstructure. It is known that crimping is caused by a non-uniform deformation in different layers of the material [26]. It is more prominent at 940°C where the wave amplitude is maximal (Fig.…”
Section: Microstructurementioning
confidence: 99%
“…In spite of the fact that folds on metallic surfaces are very interesting details of the surface deformation pattern, they did not attract much attention and were studied basically in relation to complex loading methods such as rolling (Gubernatorov et al, 1999a(Gubernatorov et al, , 1999b(Gubernatorov et al, , 2001Sokolov et al, 1995).…”
Section: Folds and Lipsmentioning
confidence: 99%
“…Many papers have been devoted to this subject especially in the field of geology (Williams et al, 1979;Huddleston, 1973;Bastida et al, 1999) while only few such papers can be found for metals (Gubernatorov, 1999a;Gubernatorov et al, 1999b;Sokolov et al, 1995). It is regrettable because folding is a frequent finding in fcc single crystals having [111] orientation with respect to the compression axis (Lychagin, 2006;Lychagin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…with colleagues had called the reason for corrugating surface distortion of the material layers. They also show that the corrugation may be formed in a structurally homogeneous material (single crystal), that is, availability of basic stress concentrators is not a prerequisite [3]. This fact is explained by the loss of stability of the material layers, which occurs due to the presence of alternating stresses in the meso-level deformation under shear constrained.…”
Section: Introductionmentioning
confidence: 99%